Chronic viral hepatitis B and C in pediatric patients: possibilities of ultrasound techniques for patients’ management - Demchyshyn, Yaroslav; Nezgoda, Iryna (ScienceRise: Medical Science, 2023)
Chronic viral hepatitis B and C have already become one of the medical and social problems of modern hepatology and paediatrics due to their high prevalence and ability to transform liver parenchyma and form additional complications. Nowadays, it is important to assess and examine patients by ultrasound techniques to estimate changes in morphometric, hemodynamic, and echoacoustic characteristics of the liver in patients with viral hepatitis B and C. The aim: to estimate ultrasound morphometric parameters and hemodynamic indexes, morphological deviations of the liver and spleen in pediatric patients with chronic viral hepatitis B and C by implementing of the system as Y. Davoudi diagnostic scale (2015) and analysis of echo-acoustic patterns. Materials and methods. 34 children were examined. 19 children with chronic viral hepatitis B and C formed group I, while 15 almost healthy children formed group II. All examined patients underwent collecting of anamnesis, general clinical examination, determination of the degree of liver fibrosis by non-invasive method (Fibrotest or fibroelastometry) and ultrasound examination of the abdominal cavity organs with the possibility of Doppler scanning. Differences at p<0.05 were considered statistically significant. Results. Obtained data showed that in patients of group, I index of Y. Davoudi grayscale was higher (2,6±0,26 U) compared with patients of group II (1,4±0,32 U) (p<0,01). Systolic blood flow velocities in the portal vein and the splenic vein were decreased in patients of group I (15,59±0,4 cm/s; 15,7±0,8 cm/s) compared with group II (17,68±0,8 cm/s; 17,54±0,42 cm/s) (p<0,05), resistance index in the hepatic artery was increased in patients of group I (0,78±0,02 IU) compared with patients of II group (0,68±0,04 IU) (p<0,05). Histogram indexes of the liver and liver-kidney region were higher in patients of group I (p<0,001). Сonclusions. Y.Davoudi diagnostic scale, hemodynamics parameters of the portal, splenic and hepatic vessels, echoacoustic patterns and other indexes could be prognostic factors which will indicate liver fibrosis progression in patients with chronic viral hepatitis B and C. The analysis of the obtained data showed that deviations in morphometric, echoacoustic and Doppler indexes of liver and spleen in paediatric patients with chronic viral hepatitis B and C were more clinically significant compared with almost healthy children and could be taken into account as liver fibrosis predictors